Evolution of kaftan in Malaysia - Mohamad, Zolina; Zainun, Norzaleha; Hasim, Nur Syazwani; Saidi, Kamarulzaman; Saidan, Suriati (2024)
Malaysia is a multiracial society country that is rich in traditions, culture, foods and clothing. Malays are the majority community of Malaysia and Islam is the official religion of this country. Baju Kurung is one of the main traditional costume in Malaysia. However, the changing times and current trends now days, gave way to kaftan designs began to sprout and gain a place among Malay women, whether from teenagers, adults to the elderly. Kaftan is seen as a style of choice that is become increasingly popular especially for the festive season such as Hari Raya Aidilfitri and also Aidiladha. It is also an option for women in Malaysia to wear it while going to work, attending parties, religious ceremonies, attending formal events, graduation ceremonies and some even make it as their daily wear. This is one of the evolution in the world of fashion clothing in Malaysia, which describes that kaftan design as meeting the criteria of an elegant, simple look but stylish and comfortable to wear.